Key performance and training parameters in primary total hip arthroplasty – an expert consensus using the Delphi technique - Howgate, DJ; Garfjeld Roberts, P; Kendrick, B; Rees, J (SAGE Publications, 2021)
Aims: Primary total hip arthroplasty (THA) is a commonly performed and successful operation which orthopaedic trainees must demonstrate competence in prior to completion of surgical training. An assessment of agreement between surgical trainers regarding the critical steps of a primary THA has never been undertaken. The aim of this study was to define and rank the key steps of a primary THA regards ease of teaching and their importance in achieving the best patient outcome.